Aortic aneurysm association with SLE – a case–control study. (August 2016) - Guy, A; Tiosano, S; Comaneshter, D; Tekes-Manova, D; Shovman, O; Cohen, A D; Amital, H
Objectives: Aortic aneurysm is a life threatening cardiovascular complication in patients with systemic lupus erythematosus (SLE).The purpose of this study was to investigate the association between SLE and occurrence of aortic aneurysms. Methods: Patients with SLE were compared with age- and sex-matched controls regarding the proportion of aortic aneurysm in a case–control study. Chi-square and t -tests were used for univariate analysis and a logistic regression model was used for multivariate analysis. The study was performed utilizing the medical database of Clalit Health Services. Results: The study included 5018 patients with SLE and 25, 090 age- and sex-matched controls. The proportion of aortic aneurysm in patients with SLE was increased compared with the proportion in controls (0.6% and 0.1%, respectively, p  < 0.001). In a multivariate analysis SLE was associated with the coexistence of aortic aneurysms (odds ratio 2.06, 95% confidence interval 1.21–3.51). Conclusions: Patients with SLE have a higher proportion of aortic aneurysms as compared with matched controls. Therefore, physicians treating patients with SLE should be aware of this life threatening association.